Marketing in the social media on the example of the social webpage of the University Library in the social networking service Facebook - Piotrowski, Dominik Mirosław (Folia Toruniensia, 2011)
The article discusses the issue of using the potential of the social media in carrying out electronic library services. It shows the strategies of optimization of social media and the methods of social marketing on the example of the fanpage of the University Library in Toruń in the service Facebook. Marketing in social media is a new field and undoubtedly it is necessary to verify the condition of research and to familiarize Polish librarians with the systematized collection of data on this subject. Thus, the article is supposed to be a guide for librarians, who need ideas to use the social service Facebook in their work. The article includes answers to many questions such as how to collect a group of loyal fans, how to organize competitions and events, how to avail the Online Public Access Catalogue of the library, how to make the social webpage look professional, and how to use the advanced functions and possibilities of Facebook.